Selected Factors that Influence on the Quality of Teaching in the Faculty of Languages, Souphanouvong University - Keoboualapheth, Soulideth; Phommaseng, Sisoury (Souphanouvong University Journal Multidisciplinary Research and Development, 2015)
This study aims to investigate the factors that influence the quality of teaching in the Faculty of Languages. 15 teachers were surveyed. The selected factors included teaching qualifications, teaching techniques, teaching experience and problems incurred. The results showed that teachers used several teaching techniques, however, some of them have minimal qualifications, are lacking in experience and there is a shortage of teaching materials. Some difficulties faced by teachers are poor internet access, limited skills, and insufficient time due to their multiple roles, large class sizes, and students with low concentration levels and willing to learn. The study suggested that various ideas were discussed to improve the quality of teaching.